Bud, Not Buddy - Curtis, Christopher Paul (New York Delacorte Prees, 1999)
Ten-year-old bud, a motherless boy living in Flint, michigan, during the great depression, escapes a bad foster home and sets out in search of the man he believes to be his father -the renowned bandleader, H. E. Calloway of grand rapids
American Corner
Winner Coretta Scott King Award
Winner The John Newbery Medal
11
Keywords: English Fiction; English Stories